Privacy-Oriented Transaction for Public Blockchain via Secret Sharing. (19th November 2022) - Mi, Bo; Wu, Bingqing; Huang, Darong; Liu, Yang; Chen, Lu; Wan, Shaohua
Abstract : Immutability and traceability are the main reasons for the popularity of blockchain. Nevertheless, its transparency also makes the transactions visible to all participants, which seriously violates the privacy of some dealers. In order to transfer accounts over blockchain, all verifiers should be empowered with the ability to confirm the transactions, leading to the conflict between extensive consensus and individual privacy. Orienting to privacy issues of UTXO (Unspent Transaction Output), this paper exploited the unconditional security of Shamir's secret sharing to construct a logic-physical map for public chain, which enabled noninteractive transaction verification without privacy infringement. A comprehensive analysis indicated that the proposed scheme is secure under UC (Universal Composability) framework with practical computation and communication overheads.